Lymphocele in a Renal Transplant Recipient During Lymphoscintigraphic Evaluation of Unilateral Leg Oedema: a Case Report - Begum, Shamim MF; Mutsuddy, Pupree; Sultana, Sadia (Bangladesh Journal of Nuclear Medicine, 2018)
Lymphocele is a common lymphatic complication in renal transplant recipient. The definition of lymphocele is a lymph-filled extraperitoneal space, with no epithelial lining. This condition may originate from leakage of lymph from unligated iliac vessels lymphatics of the recipient and/or surgical damage of the graft lymphatics during the procurement. The untreated complications may lead to catastrophic consequences. Early diagnosis and treatment of these complications are paramount to prevent graft failure and other significant morbidities to the patients. Here a case is presented in a haplotype renal transplant recipient showed abnormal radiotracer accumulation in the transplant fossa during lymphoscintigraphic evaluation with history of right lower limb swelling. Bangladesh J. Nuclear Med. 21(1): 43-45, January 2018